Understanding Audience Engagement in the Contemporary Arts - Pitts, Stephanie (Routledge Research in the Creative and Cultural Industries, 2021)
Drawing on unique multi-arts, multi-city scholarly research, Understanding Audiences for the Contemporary Arts makes a timely and urgent contribution to debates about the place of arts and culture in contemporary society. 　 The authors critically interrogate the challenges of access, diversity, privilege and responsibility in contemporary art. Asking who benefits from, pays for and consumes the arts, the book highlights fresh, forward-thinking audience and organisational attitudes that show the potential of live arts engagement to contribute to engaged citizenship. Complemented by comparative global analysis, the cutting-edge insights in this book are relevant for interdisciplinary researchers across audience studies and beyond. Enhanced by a new framework for the understanding audience engagement, the book is relevant to scholars, policymakers and reflective practitioners across the spectrum of arts and cultural industries management.